Counting and comparing - Rebecca Bristow; Valeska Becker; Rune Iversen (Documenta Praehistorica, 2025)
As Neolithic figurative finds – that is to say anthropomorphic and zoomorphic figurines, vessels, applications and impressions – were uncovered in Europe and the Near East, it was quickly apparent that they all shared common features over several millennia and thousands of kilometres: they were made of clay, usually depicted women, and were found in settlements. This led to cross-cultural comparisons and, in turn, wide-ranging interpretations regarding the use of figurative representations during the Neolithic. However, this cross-cultural approach eventually met its limits, as regional studies highlighted differences in features and distribution among various cultural groups. Figurative finds were, in fact, not spread evenly across Europe. While some areas yielded multitudes, others yielded none. This article addresses the challenges of making cross-cultural comparisons, and underlines the need for a quantitative and contextualized approach: introducing a new relational database containing more than 2500 figurative representations from Central Europe and the Balkans, we compare find densities across cultural groups and regional clusters in order to examine the development of clay figuration in Neolithic Europe.